Building Islamic polity within secular frame of political activity in Egypt, Tunisia and Turkey with reference to Ibn Khaldun’s theory of state - Ra'ees, Wahabuddin (ISTAC, 2013)
The emerging tendency among the proponents of political Islam in Egypt, Tunisia, and Turkey is that they intend to create Islamic polity within secular frame of political activity that is they are prepared to share power with secularists and preserve the secular nature of the state. The relevant question this study investigates is that does the approach of building an Islamic polity within secular frame of political activity fall within Abū Zayd ‘Abdur-Raḥmān bin Muḥammad bin Khaldūn Al-Ḥaḍrami, (27 May 1332–19 March 1406 AD) @ Ibn Khaldun’s theory of state. In Ibn Khaldun’s frame of civilization, state is a religious necessity and purposive, created by men to facilitate attainment of public interest or fundamental human rights ordained by the Lawgiver. State becomes a rational state devoid of religious orientation when it serves the interests of the ruling elites only. This study investigates if building an Islamic polity within secular frame of political activity falls within Ibn Khaldun’s religious or rational typology of state. Ibn Khanldun’s theory of state is comprehensive. The religiously pluralistic model of secularity adopted by the Islamist ruling parties in Egypt, Tunisia and Turkey and Ibn Khaldun’s religious state or regime of law focus on protections and promotion of divine rights of men (i.e. fundamental human rights). The religiously pluralistic model of secularity will seize to be in line with Ibn Khaldun’s regime of law if it seizes to protect and promote public interest.